Open and distance learning during the COVID-19 pandemic: university students’ learning experiences and academic achievements / Muhammad Hakimi Tew Abdullah, Norwati Roslim and Mohd Idzwan Mohd Salleh - Abdullah, Muhammad Hakimi Tew; Roslim, Norwati; Mohd Salleh, Mohd Idzwan (Universiti Teknologi MARA, 2022)
Universiti Teknologi MARA (UiTM) has taken an approach of Open and Distance Learning (ODL) system as a way to ensure the continuity of its education during the COVID-19 pandemic. This transformation leads to various challenges in teaching and learning. Hence, this study aimed to describe the ODL in terms of university students’ learning experiences and their academic achievements during the COVID-19 pandemic. This study involved a total of 3283 students during March-August 2020 semester in UiTM Negeri Sembilan. Data were collected via online surveys and were descriptively and statistically analysed using Statistical Package for the Social Sciences (SPSS). Findings showed that students were given sufficient information regarding the assessments of the course (mean=3.64) and the delivery of the course content (mean=3.65). The success factors on the students’ academic achievements were due to the support from lecturers (mean=2.78), peers (mean=2.79) and family (mean=2.55). Thus, it can be concluded that the majority of the students are satisfied with their ODL learning experiences and academic achievements. This study suggests that academic management should continue to provide effective support in the form of resources and services to increase performances by their students.